Reformasi Hukum Jabatan Menteri Sebagai Instrumen Revitalisasi Kabinet Profesional - Muhamad Latif; Tusi Wirahayu Pertiwi; Dwi Wisnu Kurniawan (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
Abstract The modern era demands adaptive and professional governance in order to achieve the Sustainable Development Goals (SDGs), particularly Goal 16, and to align with the Asta Cita vision and the National Research Master Plan (RIRN). However, as a background to the issue, the current situation indicates that executive governance still faces accountability challenges, as evidenced by the KPK’s 2023 data on ministerial corruption, the low Government Effectiveness Index (WGI) in 2022 at minus 0.09, and the low perception of cabinet professionalism according to the 2022 National Administrative Agency survey. Building on these issues, this study aims to analyse the urgency of legal reform regarding ministerial positions as a strategic instrument to revitalise a professional cabinet, focusing on legality, competence, and independence from conflicts of interest. The research method employed is descriptive-analytical qualitative research through literature review and document analysis sourced from legislation, scientific publications, and official government reports. The research findings indicate that the existing legal framework still contains regulatory loopholes in the selection and oversight systems, making it vulnerable to triggering maladministration and detrimental political intervention. Therefore, a conceptual model for legal reform is required that establishes the appointment of ministers based on standardised and accountable competency criteria. In conclusion, legal reform regarding ministerial appointments is a crucial instrument in revitalising a professional cabinet, as strengthening the regulations governing the appointment and dismissal of ministers will result in a competent and clean executive branch capable of strengthening state institutions that are oriented towards the public interest.